2023
DOI: 10.1097/dcr.0000000000002745
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation of Pilonidal Sinus Disease: A Pilot Study

Abstract: See video on DCR YouTube Channel at https:// youtu.be/8WpzS_10Wyk BACKGROUND: Pilonidal disease is classically treated with wide local excision, although a number of minimally invasive approaches are currently under investigation. We aimed to determine the safety and feasibility of laser ablation of pilonidal sinus disease. IMPACT OF INNOVATION:Laser ablation provides a minimally invasive means of obliterating pilonidal sinus tracts without a need for excessive tract dilation. Laser ablation can be performed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The literature review revealed that laser ablation using a 1470‐nm radial diode laser fiber is effective for the treatment of PNS because of its minimally invasive nature and is associated with reduced postoperative pain, shorter healing time, and potentially lower recurrence rates compared to traditional surgical techniques. Furthermore, few studies have reported favorable outcomes with laser ablation, including improved wound healing and lower recurrence rates [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed that laser ablation using a 1470‐nm radial diode laser fiber is effective for the treatment of PNS because of its minimally invasive nature and is associated with reduced postoperative pain, shorter healing time, and potentially lower recurrence rates compared to traditional surgical techniques. Furthermore, few studies have reported favorable outcomes with laser ablation, including improved wound healing and lower recurrence rates [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The laser vaporizes and ablates the sinus tracts while simultaneously sealing the surrounding tissue, thereby minimizing damage and promoting faster healing. This approach results in smaller wounds, reduced postoperative pain, and improved patient satisfaction [ 9 ]. Laser energy selectively targets and destroys the sinus tracts, leaving the surrounding healthy tissues intact.…”
Section: Discussionmentioning
confidence: 99%
“…Newer methods, including laser treatments and phenolisation of the sinus tract have shown promising initial outcomes in terms of reduced pain, shorter hospital stays, and improved quality of life [ [29] , [30] , [31] , [32] ]. Further investigations are required to assess the safety, recurrence rates and long-term effectiveness of these methods, especially taking into account the fact that phenol treatment is not approved in certain European countries due to concerns about its potential toxicity [ [30] , [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%